Integrating Social Funds into Local Development Strategies : Five Stories from Latin America - Serrano, Rodrigo (World Bank, Washington, DC, 2012)
The steady movement towards decentralization that Latin America has experienced in the last decade, often referred to as the "quiet revolution", has led governments and donors to rethink the role Social Funds (SFs) should play in promoting local development. While SFs had been relatively successful in building local infrastructure, insufficient integration with public sector systems (both national and local) had raised well founded concerns about institutional and investment sustainability. This Note gives a quick overview of how reforms are unfolding in five SFs in Latin America, and highlights some features of the emerging models. It shows that many SFs are working closely with local governments. For these SFs the challenge is no longer whether they undermine local governments or not but rather how they can become an effective instrument of the country's decentralization policy-i.e., how their interactions with local governments, communities, and sectoral agencies advance the decentralization policy objectives and a more balanced approach to local development.